2023
DOI: 10.3390/foods12061234
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Composition of Selected Street Foods Commonly Available in Malaysia

Abstract: Despite growing evidence of increased saturated and trans fat contents in street foods, little is known about their fatty acid (FA) compositions. This study aimed to analyse the saturated fatty acids (SFAs), monounsaturated fatty acids (MUFAs), polyunsaturated fatty acids (PUFAs), and trans fatty acids (TFAs) content of 70 selected and most commonly available street foods in Malaysia. The street foods were categorised into main meals, snacks, and desserts. TFAs were not detected in any of the street foods. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
(96 reference statements)
1
1
0
Order By: Relevance
“…In this study, all street foods contained TFAs, less than 2% of total fatty acids. Similar studies on fatty acid compositions of street foods in Asia, including India [5], Malaysia [61], and Central Asia [62][63][64], have reported the presence of TFAs in RTE street foods. Higher TFA contents (0.29-22.96% of total fatty acids) are present in street foods from India, while TFA was not detected in street foods from Malaysia.…”
Section: Total Fat Content and Fatty Acid Compositionsupporting
confidence: 61%
See 1 more Smart Citation
“…In this study, all street foods contained TFAs, less than 2% of total fatty acids. Similar studies on fatty acid compositions of street foods in Asia, including India [5], Malaysia [61], and Central Asia [62][63][64], have reported the presence of TFAs in RTE street foods. Higher TFA contents (0.29-22.96% of total fatty acids) are present in street foods from India, while TFA was not detected in street foods from Malaysia.…”
Section: Total Fat Content and Fatty Acid Compositionsupporting
confidence: 61%
“…Higher TFA contents (0.29-22.96% of total fatty acids) are present in street foods from India, while TFA was not detected in street foods from Malaysia. In India, vegetable ghee with high TFAs (2.5-29.9% of fatty acids) was mainly used for deep-frying and frying [5], and in Malaysia, palm oil and tub margarine, which do not contain TFAs, are used for frying [61]. Also, a review on the influence of heating during cooking on the TFA content of edible oils reported that TFAs were not produced during the heating of edible oils below 200 °C [65].…”
Section: Total Fat Content and Fatty Acid Compositionmentioning
confidence: 99%